Final oocyte maturation discharge with either human chorionic gonadotropin or GnRH agonist in oocyte donors: cohort retrospective analysis - Portella, Jimmy (2014)
The GnRH antagonists (GnRHant) protocol has allowed the use of GnRH agonist (GnRHa) as inductor of ovulatory discharge (OD) replacing human chorionic gonadotropin (hCG). An important advantage of GnRHa use in OD is that it significantly decreases the risk of ovarian hyperstimulation syndrome (OHSS) due to its luteolytic effect, important in cases of oocyte donors. Objectives: To compare proportion of oocytes obtained, oocyte/embryo  quality, reproductive result and OHSS incidence in consecutive oocyte donation cycles when OD was done with hCG or GnRHa. Cycles with preimplantation genetic diagnosis were compared. Design: Cohort retrospective study. Setting: Grupo PRANOR, Clinica Concebir, Lima, Peru. Participants: Oocyte donors and receptors. Interventions: A GnRHant protocol was used in 43 oocyte donors for 203 consecutive stimulation cycles and OD with hCG (n=127) or GnRHa (n=76) based in clinical decision and follicular count. Oocytes were assigned either to an oocyte bank (vitrification) or to 303 cycles of oocyte receptors. Main outcome measures: Oocytes aspired, fecundation rate, embryo quality, blastocyst formation. Results: There were significant differences in number of oocytes aspired in favor of the GnRHa group with regards to the hCG group (24.09±12.24 versus 18.69±8.93, p=0.002 respectively). There were no significant differences among the groups compared in the global result of mature oocytes proportion, fecundation rate, embryo qulity, blastocyst formation. The proportion of chromosomically normal embryos was similar between GnRHa (35.2%) and hCG (34.53%) groups, and pregnancy (64.49% versus 62.59%), implantation (45.41% versus 42.38%) and abortion (8.7% versus 8.7%) global rates were comparable. OHSS incidence reduced significantly in the OD group with GnRHa (0%) compared with the hCG group (18.9%, p<0.0001). Conclusions: OD with GnRHa is a safe and efficacious method to use in patients with high risk of OHSS such as oocyte donors, as it completely eliminates OHSS. Embryo quality and reproductive results were identical between OD groups with GnRHa and hCG.